School-based management practices, principal leadership and school performance - Romero, Danilo M. (2008)
This study determined the significant effects of the implementation of school-based management and the principals' school leadership experience on school performance. It made use of the survey and case study method. It was concluded that limited compliance in the pilot stage implementation of the SBM milestones temporarily restricted the extent of the decentralization of education. Also, the limited extent of the implementation of the SBM milestones, from the basic up to the intermediate and advanced stages, is not sufficient to cause school performance to improve. The principals' leadership experience takenalone or even when joined with the limited implementation of SBM does not influence school performance. Sustained and full implementation of SBM milestones for a period longer than two years and a genuine principals' role in ensuring student achievement through an unwavering emphasis on "leadership for student learning" may be required to improve school performance.
Thesis (Ph.D. Educational Administration)--University of the Philippines, Diliman.
Keywords: School-based management -- Philippines -- National Capital Region; School management and organization -- Philippines -- National Capital Region; High school principals -- Rating of -- Philippines -- National Capital Region; Educational leadership -- Philippines -- National Capital Region; High schools -- Philippines -- National Capital Region -- Administration; Public schools -- Philippines -- National Capital Region -- Administration; Education, Secondary -- Philippines -- National Capital Region -- Evaluation